In-situ synthesis of novel plate-like Co(OH)2 co-catalyst decorated TiO2 nanosheets with efficient photocatalytic H2 evolution activity. (7th September 2017) - Xu, Hao; Li, Songsong; Ge, Lei; Han, Changcun; Gao, Yangqin; Dai, Dongsheng
Abstract: Efficient separation of photo-generated electrons and holes is a crucial aspect for photocatalytic hydrogen evolution. Herein, novel plate-like Co(OH)2 decorated TiO2 nanosheets for photocatalytic water splitting were synthesized by a facile in-situ synthetic method. The results of X-ray diffractometry (XRD), transmission electron microscope (TEM), UV–Vis diffusion reflectance spectroscopy (DRS) and X-ray photoelectron spectroscopy (XPS) indicate the successfully incorporation of Co(OH)2 co-catalysts onto the surface of TiO2 nanosheet photocatalysts. Further photocatalytic hydrogen evolution experiments illustrate that all Co(OH)2 decorated TiO2 samples show higher rate of hydrogen production performance than pure TiO2 sample and the composite sample with Co(OH)2 loading amount of 0.5mol% presents the highest photocatalytic hydrogen production activity of 746.93 μmol g −1 ·h −1 . It is indicated that plate-like Co(OH)2 particle act as an electron collector, which leads to photo-generated electrons transfer from TiO2 to Co(OH)2, and therefore enhance the photocatalytic activity. Based on above results, a possible mechanism is proposed and further verified by surface photovoltage spectra (SPV). Graphical abstract: Highlights: Plate-like Co(OH)2 as a promising earth-abundant and low cost co-catalyst to enhance photocatalytic H2 evolution activity. The plate-like Co(OH)2 /TiO2 nanosheets composite shows significantly enhanced H2 evolution activity. The intimate interfaces promote the charge transfer and separation. The mechanism is proposed and confirmed by surface photovoltage (SPV) measurement.